Analisis Hukum Undang-Undang No. 27 Tahun 2022 Tentang Pelindungan Data Pribadi (Putusan No. 597/Pid.Sus/2021/Pn.Jkt.Pst) - Arthawijaya, Andhika; Laksanto Utomo, Stefanus; L. Luntungan, Benjamin (Sekolah Tinggi Ilmu Hukum Prof Gayus Lumbuun, 2024)
The background to this research is based on the problem of changes in the lifestyle of Indonesian people due to the development of information technology. Which causes significant changes in the socio-cultural, economic and legal framework. The main problem is that this change has made the potential for a digital economy to grow which is quite large, but is accompanied by several negative impacts, including threats to citizens' rights and privacy and personal data. The purpose of this study is to find out the legal arrangements for Personal Data Protection in Indonesia, as well as to find out the form of legal protection for Personal Data in the event of a violation of the law in its application in the field. The research method is to use normative juridical research using a statutory approach and a conceptual approach. The data collection method used was literature study and analyzed prescriptively. The conclusions and results of this study indicate that in Indonesia there are several rules governing the protection of personal data. However, these regulations are still not optimal in protecting the confidentiality of a person's personal data. For this reason, preventive and repressive efforts are needed in legal protection if personal data is misused. Preventive efforts, namely legal protection that is preventive before the failure of the protection of consumer personal data which can cause harm to consumers. Meanwhile, repressive efforts in protecting personal data are carried out by involving the role of the government in providing legal protection due to losses suffered by owners of personal data due to failure to protect the confidentiality of their personal data.